TAREKAT-TAREKAT DI KALIMANTAN SELATAN ( Alawiyyah, Sammniyyah dan Tijniyyah ) - Asmaran Asmaran (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2013)
There is no doubt that islamization of Nusantara can not be separated from significant role of sufism. The term "wals" in Indonesia, for example, refers to preachers or spreaders of Islam in the earlies periods of its history, and with same meaning the "datu" in South Kalimantan, such as Datu Kelampayan (attributed to the prominent Islamic leader, 'lim, Muhammad Arsyad al-Banjr). Based on this historical background, it is not strange that sufi orders developed rapidly in South Kalimantan. According to the scientific researches conducted, in South Kalimantan found Junaidiyyah, Naqsabandiyyah, Naqsabandiyyah-Khalidiyyah, Qadiriyyah-Naqsabandiyyah, Alawiyyah, Sammniyyah, and Tijniyyah. This article is discussion on the three latter orders; some of them took root in ulama's networks in middle east, but the others in Java